Pre-operative DNA methylation marks as predictors of weight loss outcomes after sleeve gastrectomy - Guillermo Paz-López; Teresa M. Linares-Pineda; Andrés González-Jiménez; Raquel Sancho-Marín; Luis Ocaña-Wilhelmi; Francisco J. Tinahones; Sonsoles Morcillo; Carolina Gutiérrez-Repiso (Molecular Metabolism)
Objective: Although DNA methylation has been suggested to be a potential predictor of the progression of obesity and obesity-related diseases, little is known about its potential role as predictive marker of successful weight loss after bariatric surgery. Methods: 20 patients who underwent sleeve gastrectomy were classified according to the percentage of excess weight loss (%EWL) 1 year after bariatric surgery, using 60% as the cut-off point. Blood DNA methylation was analyzed prior to surgery using the Infinium Methylation EPIC Bead Chip array-based platform. Results: A total number of 76,559 differentially methylated positions (DMPs) (p < 0.05) were found between <60% EWL and >60% EWL groups. Of them, 59,308 DMPs were annotated to genes. KEGG enrichment analysis showed that pathways involved in the signalling of MAPK, Wnt, mTor, FoxO and AMPK, among others, were involved in weight loss trajectory.A stepwise logistic regression using the DMPs with an absolute Δβ >0.2 showed that higher methylation levels in the CpG sites cg02405213 (mapping to JAK2) (OR: 1.20098, [0.9586, 1.5044]) and cg01702330 (OR: 2.4426, [0.5761, 10.3567]), were shown to be associated with a higher probability of achieving >60 %EWL after sleeve gastrectomy, whereas higher methylation levels in the CpG site cg04863892 (mapping to HOXA5) were associated with lower probability of achieving >60 %EWL after sleeve gastrectomy (OR: 0.7966, [0.5637, 1.1259]). Conclusions: Our results show a different pre-surgery methylation pattern according to %EWL. We identified three CpG sites (cg04863892, cg02405213, cg01702330) with potential value as predictor markers of weight loss response to bariatric surgery.